“Caínes despiadados… Caínes invasores”. The Invasión of December 10, 1948, to Costa Rica in a National and Transnational Perspective - Ugalde Quesada, Alexia (2020)
This article studies the invasion of Costa Rica on December 10, 1948 in its dimensions of national conflict, which is, as a consequence of the civil war of the same year and of transnational conflict involving other countries in the region as well as the intervention of the Organization of American States. For this, historical sources from the National Archive of Costa Rica, documents from the Central Intelligence Agency, the National Archives of the United States, and national press were consulted. It is argued that during Costa Rican postwar, political violence remained due to the victors. They created institutions and legislation to persecute their enemies, which caused an inminent invasion.